New technique for the implementation of nonlinear models for microwave transistors for broadband data communication - Rafael-Valdivia, Guillermo (2015)
A new way to implement nonlinear models for microwave transistors is shown. It allows conventional drain current functions and conventional equivalent circuits to enhance their capabilities in order to predict the frequency dispersion.